2018
DOI: 10.1055/s-0037-1618328
|View full text |Cite
|
Sign up to set email alerts
|

Study of Relationship between Central Venous Pressure and Peripheral Venous Pressure during Intraoperative Period in Neurosurgical Patients

Abstract: IntroductionPatients undergoing neurosurgery are at risk of significant blood loss and resulting hemodynamic changes. In case of sudden blood loss, volume of blood in arteries is maintained at expense of that in veins, manifesting as low central venous pressure (CVP) 1 associated with tachycardia initially and, a fall in arterial pressure is a late sign of hypovolemia. Monitoring of CVP is, therefore, of great assistance during hypovolemia.CVP is the pressure within the intrathoracic venae cavae, measured by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Practicing a modern hemodynamic observation method at the stand of evidence and scientific reasoning will open a new gateway to less complicated yet effective critical care to patients [1].Some studies were conducted among critically ill patients and found the agreement's degree is a high between CVP and PVP [1,22]. Stated the monitoring of PVP could be utilized as a normal, priceimpacting as well as a minimum intrusive alternative to monitoring the CVP and with low morbidity complications [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Practicing a modern hemodynamic observation method at the stand of evidence and scientific reasoning will open a new gateway to less complicated yet effective critical care to patients [1].Some studies were conducted among critically ill patients and found the agreement's degree is a high between CVP and PVP [1,22]. Stated the monitoring of PVP could be utilized as a normal, priceimpacting as well as a minimum intrusive alternative to monitoring the CVP and with low morbidity complications [23,24].…”
Section: Introductionmentioning
confidence: 99%